Diastolic function in patients with preeclampsia during pre- and post-partum period using tissue doppler imaging (Faculty of Medicine Universitas Indonesia, 2016)
Background: Prior studies have compared the E/e’ elevation in preeclampsia patients to normal patients, however there are no data whether this elevation persists after birth. The aim of this study is to analyze diastolic function in preeclampsia patients during pre- and post-partum period using E/e’ parameter measurement. Methods: This is a prospective cohort study of pregnant women with preeclampsia who were hospitalized and planned for pregnancy termination. Basic clinical characteristics were obtained from all samples. Echocardiography was done prepartum, 48-72 hours after termination, and 40-60 days postpartum. Post hoc analysis using least significant difference method was used to compare the results between measurements. Results: 30 subjects were enrolled in the study. Analysis on E/e’ characteristics showed statistical difference between prepartum E/e’ and 40 days postpartum E/e’ (11.87±3.184 vs 9.43±2.529, p=0.001, CI=1.123-3.751), as well as between 48 hours post-partum and 40 days post-partum period (12.12±2.754 vs 9.43±2.529, p<0.001, CI=1.615-3.771). There were no statistical differences between pre-partum E/e’ and 48 hours post-partum E/e’ (11.87±3.184 vs 12.12±2.754, p=0.633, CI=-1.345-0.832). Conclusion: This study showed diastolic dysfunction in preeclampsia patients persists up until a few days after birth, but resolves in time (40 days after birth) as measured by tissue doppler imaging.